The hungry athlete - Relative energy deficiency in sport (RED-S) - Guzman, A. (2020)
Some information on Relative Energy Deficiency in sport (or RED-s), the syndrome, which can impact bone health, reproductive hormones, immunity and metabolic rate, as well as many more physiological functions.